When information about one's counterpart matters: Prevention focus increases the impact of counterpart cues on negotiation behavior. Issue 2 (10th January 2020) - Giacomantonio, Mauro; ten Velden, Femke S.; De Cristofaro, Valeria; Beersma, Bianca
Abstract : Purpose: To avoid (costly) conflict, it is imperative to uncover when negotiators cooperate. The previous study has shown that negotiators' cooperative or competitive behavior is oftentimes guided by cues about their counterpart; information about his/her traits or behavior. Using regulatory focus theory, this paper aims to investigate when this is likely to happen. The authors hypothesize and test that because prevention focus (rather than promotion focus) is associated with concerns for safety and concrete surroundings, it strengthens the impact of counterpart cues. Design/methodology/approach: The authors used two scenario studies and one behavioral negotiation study to test the general hypothesis. The authors measured or manipulated participants' regulatory focus, manipulated counterpart cues by varying the information negotiators received about their counterpart's traits and behavior, and measured participants' cooperative or competitive concession making behavior. Findings: Results from the studies confirmed that under prevention focus, negotiators' cooperative behavior depended on whether they received cooperative versus competitive counterpart cues more than under promotion focus. Furthermore, results also showed that under prevention focus, negotiators' behavior was relatively unaffected by their own social motivation – i.e. their personal goal to obtain favorable outcomes for oneself or for both negotiation parties. Originality/value: By showing that regulatory focus determines when counterpart cues affect negotiation behavior, this paper furthers the understanding of when contextual factors affect negotiators' behavior. In addition, it contributes to the understanding of the complex effects of prevention focus in interpersonal behavior.